Instructor's Guide to accompany Electrical Wiring Industrial - Smith, Robert L. (Thomson Delmar Learning, 2008)
Updated to reference the 2008 National Electrical Code, this edition of Electrical Wiring Industrial guides readers step-by-step through the wiring of an entire industrial building, making this an ideal resource for anyone who will work in the industrial electricity industry. With a practical, straightforward approach, the book begins by covering the tasks and responsibilities that face today's professional industrial electricians, including: installation of electrical service, power and lighting; special new construction systems; changeovers from old systems; planning for growth and increased capacity; and periodic maintenance procedures. Specific references to the 2008 National Electrical Code throughout the book shows readers how to incorporate codes and principles into everyday practice and procedures. A complete set of industrial building plans is also included, offering opportunities for hands-on practice in interpreting and applying Code requirements to sitework, feeder bus systems, panelboards, fiber optics, harmonics, hazardous locations, and more